Total body water measured by desiccation and by tritiated water in adult rats - A. Tisavipat (2018)
Total body water (TBW) of 32 adult rats, 16 males and 16 females, was measured indirectly with tritium dilution and directly by desiccation in the same animal. There was no difference between the sexes; therefore the data were combined. The TBW of adult rats, whose mean weight in grams was 168.4 ± 2.76 SE, measured with tritium was 74.4 ± 1.78% of body weight and by desiccation it was 66.4 ± 0.28%; on a fat free wet weight (FFWW) basis, tritium measured a volume of 83.5 ± 1.43%, and desiccation, 76.0 ± 0.54%. The difference between the 2 methods, whether expressed as percentage of FFWW or body weight, was significant at P < 0.001.